Spatiotemporal distribution of boron in the groundwater and human health risk assessment from the coastal region of Bangladesh - Rahman, Mahfuzur; Tushar, Mahmud Al Noor; Zahid, Anwar; Ahmed, Kazi Matin Uddin; Siddique, Mohammad Abdul Momin; Mustafa, M Golam (Environmental science and pollution research international, 2021)
High concentrations of naturally-occurring and man-accentuated boron in groundwater possess a potential threat to the health and well-being of humans worldwide. In Bangladesh, only a few studies focused on the health risks of boron-containing groundwater. Therefore, the present study investigated the spatiotemporal distribution of boron concentrations in groundwater and its associated health risks in the coastal districts of Bangladesh. A total of 268 samples from the shallow and deep wells during the wet and dry season (137 and 131 samples, respectively) were collected to determine the level of boron concentrations and health risk status. The groundwater boron concentrations ranged from 0 to 4.10 mg/L with an average concentration of 0.68 mg/L, which was much lower than the WHO and the values of Bangladesh drinking water standard guideline. The boron concentrations in the shallow wells override the deep ones with insignificant seasonal variation. Boron contamination affected 10% of the shallow wells in the wet season and only 6% of them in the dry season, whereas only 1% of deep wells exceeds the WHO guideline values of 2.40 mg/L during the wet and dry season, respectively. The human health risk of boron was determined by computing estimated daily intake (EDI) and hazard quotient (HQ) values for infants, children, teenagers, and adults. The average HQ value delimitated that children have high risk followed by teenagers, adults, and infants. About 90-95% of the studied samples were free from boron contamination because of having HQ values < 1 and the rest of the samples possess a high risk for children. For the overall study area, the deep wells were found safer than the shallow wells, which were more susceptible to boron contamination aided by localized freshwater inputs.
Keywords: Bangladéš; podzemní voda; Groundwater; Infant; Humans; kojenec; Boron enrichment; dítě; Pearson correlation; Child; Environmental Monitoring; Hazard quotient; dospělí; lidé; mladiství; Adult; monitorování životního prostředí; Health risk; Male; Boron; Adolescent; Water Pollutants, Chemical; Coastal zone of Bangladesh; Bangladesh; Risk Assessment; mužské pohlaví; hodnocení rizik; bor; chemické látky znečišťující vodu